Genome-wide identification of genic and intergenic neuronal DNA regions bound by Tau protein under physiological and stress conditions. Issue 21 (13th October 2018) - Benhelli-Mokrani, Houda; Mansuroglu, Zeyni; Chauderlier, Alban; Albaud, Benoit; Gentien, David; Sommer, Sabrina; Schirmer, Claire; Laqueuvre, Lucie; Josse, Thibaut; Buée, Luc; Lefebvre, Bruno; Galas, Marie-Christine; et al.
Abstract: Tauopathies such as Alzheimer's Disease (AD) are neurodegenerative disorders for which there is presently no cure. They are named after the abnormal oligomerization/aggregation of the neuronal microtubule-associated Tau protein. Besides its role as a microtubule-associated protein, a DNA-binding capacity and a nuclear localization for Tau protein has been described in neurons. While questioning the potential role of Tau-DNA binding in the development of tauopathies, we have carried out a large-scale analysis of the interaction of Tau protein with the neuronal genome under physiological and heat stress conditions using the ChIP-on-chip technique that combines Chromatin ImmunoPrecipitation (ChIP) with DNA microarray (chip). Our findings show that Tau protein specifically interacts with genic and intergenic DNA sequences of primary culture of neurons with a preference for DNA regions positioned beyond the ±5000 bp range from transcription start site. An AG-rich DNA motif was found recurrently present within Tau-interacting regions and 30% of Tau-interacting regions overlapped DNA sequences coding for lncRNAs. Neurological processes affected in AD were enriched among Tau-interacting regions with in vivo gene expression assays being indicative of a transcriptional repressor role for Tau protein, which was exacerbated in neurons displaying nuclear pathological oligomerized forms of Tau protein.